Dielectric Studies on Cyclohexanone and 1,4-Dioxane - Thapa, B; Shrestha, P; Bhattarai, P; Pokharel, B (Scientific World, 2013)
No abstract available Scientific World, Vol. 11, No. 11, July 2013, page 13-16